Trends in the development process of clinical practice guidelines: a questionnaire survey for the guideline development groups in Japan - Yosuke Hatakeyama; Kanako Seto; Koki Hirata; Ryo Onishi; Kunichika Matsumoto; Tomonori Hasegawa (BMC, 2022)
Abstract Background Clinical practice guidelines (CPGs) are representative methods for promoting healthcare standardization and improving its quality. Previous studies on the CPG (published by 2006) development process in Japan reported that the involvement of experts and patients, efficient evidence collection and appraisal, and paucity of evidence on Japanese patients should be improved for the efficient CPG development. This study aimed to clarify the trends of CPG development process in Japan, focusing on the involvement of experts and patients, efficient evidence collection and appraisal, and paucity of Japanese evidence. Methods A cross-sectional questionnaire survey was conducted for CPG development groups to collect information on the development activities of the CPGs published from 2012 to 2019. These CPGs were identified from the Japanese guideline clearinghouse. The questionnaire included the questions on composing the group, securing funding sources, collecting and appraising the research evidence, and the difficulties in the CPG development process. The questionnaires were distributed to the chairpersons of the CPG development groups through postal mail from November 2020 to January 2021. Combining the data from the current survey with those of previous studies reporting the development process of CPGs published by 2011, we analyzed the trend in the CPG development process. Results Of the total 265 CPGs included in the analysis, 164 (response rate: 41.4%) were from the current survey and 101 (response rate: 44.5%) were from previous studies. Among these, 40 (15.1%) were published by 2005, 47 (17.7%) in 2006-2010, 77 (29.1%) in 2011-2015, and 101 (38.1%) in 2016-2019. The proportion of CPGs involving methodologists did not increase through the publication periods. The proportion of CPGs involving patients almost doubled from the first period (15.9%) to the fourth period (32.4%). The yield rates of the articles did not change through the publication periods. The difficulty in "Coping with the paucity of Japanese evidence" has been improving consistently (69.2% in the first period to 37.4% in the fourth period). Conclusions Our results suggest the need for methodological improvement in the efficient collection and appraisal of evidence and in the system assigning experts to the CPG development groups.